A core–shell liquid metal-Cu nanoparticle with glutathione consumption via an in situ replacement strategy for tumor combination treatment of chemodynamic, microwave dynamic and microwave thermal therapy. (20th May 2022) - Yu, Yongnian; Wu, Qiong; Niu, Meng; Gou, Li; Tan, Longfei; Fu, Changhui; Ren, Xiangling; Ren, Jun; Zheng, Yongfa; Meng, Xianwei
Abstract : A stable core–shell spherical "storage pool" was obtained, which could realize the combination of chemodynamic, microwave dynamic and microwave thermal therapy. Abstract : The presence of high content glutathione (GSH) provides an effective "protective shield" for tumor cells, which undoubtedly is a huge impediment to reactive oxygen species (ROS)-based treatment. Fortunately, divalent copper (Cu 2+ ) can not only consume GSH, destroying the protection mechanism of GSH, but also can be reduced to Cu + with excellent Fenton-like reaction activity. Hence, capitalizing on the properties of liquid metals, we introduced Cu with three different valances via an in situ replacement reaction. A stable core–shell liquid-metal based "Cu storage pool" was obtained. It can effectively deplete GSH within the cells, and simultaneously produce ·OH through a Fenton-like reaction, further improving the effect of chemodynamic therapy (CDT). Under microwave irradiation, it is also capable of producing a large amount of ROS to promote tumor treatment. In addition, the loading of ionic liquid endows LZC@IL nanoparticles with certain microwave heating performance, which is able to augment microwave thermal therapy (MWTT). With the combination of CDT, microwave dynamic therapy (MDT) and MWTT, LZC@IL has an excellent effect on tumor elimination. This work offers a new idea for the application of liquid metals and the combined treatment of tumors, which has potential application value.